Miniaturized Dynamic Reconfigurable FSS With Multimode Operation and Polarization Control - Akan, Aygun; Keskin, Sena E. B.; Tokan, Nurhan T. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
This letter presents a multimode, miniaturized frequency-reconfigurable frequency selective surface (MR-FSS) capable of switching between passbands centered at approximately 1.9 GHz, 4.9 GHz, and 5.8 GHz, as well as stopbands at approximately 2.4 GHz, 3.5 GHz, and 5.8 GHz. By changing the state of the RF PIN diodes, the proposed MR-FSS provides flexible polarization control and can operate in either a bandstop mode or a bandpass mode. This enables it to function as a reflective or transparent structure. The proposed design involves metallic patterns imprinted on both sides of a single-layer RO5880 substrate, with RF-PIN diodes placed on both the top and bottom sides to achieve the desired multimode switching functionality. With multiband reconfigurability and polarization selectivity, the proposed miniaturized R-FSS enables electromagnetic shielding and dynamic frequency control for 5G systems, Internet of Things (IoT) networks, and military radar applications.
Keywords: PIN photodiodes; Frequency control; Switches; TV; Passband; Schottky diodes; Insertion loss; Geometry; 5G mobile communication; Reflection; Frequency-reconfigurable; frequency selective surface (FSS); miniaturized; multimode; polarization selection; FREQUENCY-SELECTIVE SURFACE; DUAL-BAND FSS; ELEMENTS; Engineering; Telecommunications